2010
DOI: 10.1016/j.icrp.2012.03.001
|View full text |Cite|
|
Sign up to set email alerts
|

Radiological Protection in Fluoroscopically Guided Procedures Performed Outside the Imaging Department

Abstract: An increasing number of medical specialists are using fluoroscopy outside imaging departments, but there has been general neglect of radiological protection coverage of fluoroscopy machines used outside imaging departments. Lack of radiological protection training of those working with fluoroscopy outside imaging departments can increase the radiation risk to workers and patients. Procedures such as endovascular aneurysm repair, renal angioplasty, iliac angioplasty, ureteric stent placement, therapeutic endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
148
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(161 citation statements)
references
References 144 publications
(230 reference statements)
4
148
1
8
Order By: Relevance
“…Nearly one quarter of the residents in the survey did not know this. Medical personnel can prevent themselves from radiation by increasing the distance from the source of radiation or by leaving the operating room, if not actively involved in the procedure, when the radiation is being used [9]. We found that only about a quarter practiced this routinely.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Nearly one quarter of the residents in the survey did not know this. Medical personnel can prevent themselves from radiation by increasing the distance from the source of radiation or by leaving the operating room, if not actively involved in the procedure, when the radiation is being used [9]. We found that only about a quarter practiced this routinely.…”
Section: Discussionmentioning
confidence: 89%
“…They are made up of lead and decrease the amount of radiation received by the operator. Commonly a 0.5 mm lead shield is used [9]. Nearly one quarter of the residents in the survey did not know this.…”
Section: Discussionmentioning
confidence: 99%
“…19 The maximum recommended occupational dose limit is 20mSv averaged over five years with no more than 50mSv in any one year. The ICRP also advocates three fundamental principles: justification, optimisation of protection and dose limitation.…”
Section: Radiation Guidancementioning
confidence: 99%
“…The ICRP recommended configuration when using fluoroscopy is to have the intensifier above and the x-ray tube below the patient. 19 The operating personnel should always stand on the intensifier side as this reduces the amount of radiation received by a tenth. The use of additional protective devices such as thyroid collars and goggles should be considered, especially when operating on larger patients as patient size increases the skin dose and scattered radiation.…”
Section: Radiation Guidancementioning
confidence: 99%
“…The many factors modulaing the dose in the cardiac cath lab are summarized in Table 2 and can reduce the dose by a factor of 10 to 100 [16][17][18] .…”
mentioning
confidence: 99%